THE EFFECT OF BIOFERTILIZER FORMULATION TO ZOOPLANKTON ABUNDANCE AT Channa sp. POND IN THE PEAT SOIL - Muhammad Nailizzafir; Syafriadiman Syafriadiman; Saberina Hasibuan (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
AbstracThis research was conducted on February until March 2018, in the peat soil of ponds at Petani Nenas Street, Kualu Nenas Village, Kampar District, Riau Province. The zooplankton abundance of observation have been done at the Laboratory Environment Quality of Aquaqulture, Fisheries and Marine Faculty. The aim of this research was to know the best dose of biofertilizer formulation to increase the zooplankton abundance in the peat soil of ponds and the growth of Channa sp. The methods used the and Completely Randomized Design (CRD), one factor with five treatments. The factors of B0 (without giving the biofertilizer), B1 (the dose of biofertilizer 300 g/m3), B2 (the dose of biofertilizer 450 g/m3), B3 (the dose of biofertilizer 600 g/m3), B4 (the dose of biofertilizer 750 g/m3). The best treatment of this research was B4 (the dose of biofertilizer 750 g/m3) with 6705 ind/L zooplankton abundace. specific growth rate of Channa sp. 5,58 %, absolute growth rate 8,49 g, and the survival rate 75 %. The water quality parameters in this research is good, especially of temperature 26-32 ˚C, pH 6-8, dissolve oxygen 3,7-7,1 mg/l, CO2 19,17-25,56 mg/l, nitrate 1,41-4,31, and orthoposfat 1,51- 4,31.Keywords : Biofertilizer, zooplankton abundance, peat soil, Channa sp.